The Great Mexican Emigration - Hanson, Gordon H; McIntosh, Craig (The Review of Economics and Statistics, 2010)
In this paper, we examine net emigration from Mexico over the period 1960 to 2000. The data are consistent with labor supply shocks having made a substantial contribution to Mexican emigration, accounting for two-fifths of Mexican labor flows to the United States over the last two decades of the twentieth century. Net emigration rates by Mexican state birth year cohort display a strong positive correlation with the initial size of the Mexican cohort relative to the corresponding U.S. cohort. In states with long histories of emigration, the effects of cohort size on emigration are relatively strong, consistent with the existence of preexisting networks.